Does own experience affect perception of others’ actions in capuchin monkeys (Cebus apella)? - Kuroshima, Hika; Kaiser, Ingrid; Fragaszy, Dorothy M. (Animal cognition, 2014)
Anticipating another’s actions is an important ability in social animals. Recent research suggests that in human adults and infants one’s own action experience facilitates understanding and anticipation of others’ actions. We investigated the link between first-person experience and perception of another’s action in adult tufted capuchin monkeys (Sapajus apella spp., formerly Cebus apella spp.). In Experiment 1, the monkeys observed a familiar human (actor) trying to open a container using either a familiar or an unfamiliar action. They looked for longer when the actor tried to open the container using a familiar action. In Experiment 2, the actor performed two novel actions on a new container. The monkeys looked equally at the two actions. In Experiment 3, the monkeys were trained to open the container using one of the novel actions in Experiment 2. After training, we repeated the same procedure as in Experiment 2. The monkeys looked for longer when the actor manipulated the container using the action they had practiced than when she used the unfamiliar action. These results show that knowledge derived from one’s own experience impacts perception of another’s action in these New World monkeys.
Gesehen am 05.01.2021